Cleantioides vonprahli, a new species of idoteid isopod (Crustacea: Isopoda: Idoteidae) from Bahía Málaga, Pacific Coast of Colombia - Ramos, Gabriel E. (1988)
Cleantioides vonprahli n. sp. is described from Bahía Málaga, Colombia. It was captured in bottom trawlings, with amphipods and another idoteid isopod: Cleantioides occidentalis (Richard son 1899). This new species is closest to C. planicauda (Richardson 1899) and C. occidentalis, but can be distinguished from the first species by the number of articles on the maxillipedal palp, and the second species by the shape of pleotelson. The present paper is the first record of idoteid isopods from the Colombian Pacific waters.